2013
DOI: 10.1007/s00431-013-2067-7
|View full text |Cite
|
Sign up to set email alerts
|

Use of social networking sites by parents of very low birth weight infants: experiences and the potential of a dedicated site

Abstract: The support of parents of hospitalized preterm infants by neonatal nurses and doctors could be extended by developing an expert-controlled, online networking site providing reliable and updated information and facilitating personal exchange among parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 22 publications
1
34
0
2
Order By: Relevance
“…Debate surrounds mhealth initiatives in part due to regulatory concerns (Cortez et al, 2014) and a lack of scientific evidence for improved care, outcomes, or cost savings, especially around newborn health (Agarwal and Labrique, 2014). NICU parents are already using the internet as a resource (De Rouck and Leys, 2011), however, with most agreeing there is useful information available on premature infants (Gabbert et al, 2013). Providing a scientific foundation and evidence of the usefulness of these technologies is therefore incumbent on researchers and health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Debate surrounds mhealth initiatives in part due to regulatory concerns (Cortez et al, 2014) and a lack of scientific evidence for improved care, outcomes, or cost savings, especially around newborn health (Agarwal and Labrique, 2014). NICU parents are already using the internet as a resource (De Rouck and Leys, 2011), however, with most agreeing there is useful information available on premature infants (Gabbert et al, 2013). Providing a scientific foundation and evidence of the usefulness of these technologies is therefore incumbent on researchers and health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…One way to achieve this is through the provision of mobile device‐friendly social technology and web‐based content, which are increasingly being used in health care for patient information and support . Gabbert et al surveyed 141 parents of very low birthweight infants in Germany and found all respondents said they used the Internet with 80% using it at least once every day. When searching for information during the stay in the neonatal intensive care unit (NICU) and after discharge, most parents used Google search engines.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently searched topics were “specific medical problems associated with prematurity,” “general information on prematurity” and “outcome of preterm infants”. While parents considered the Internet a useful source of information on prematurity after discharge home, only 20% felt that their questions had been fully answered online …”
Section: Introductionmentioning
confidence: 99%
“…6 This is not isolated to Canada, as German parents (n = 141) of very low birth weight infants reported to have searched for information online regarding pregnancy or prematurity similarly during pregnancy (75.2%), hospitalization (68.6%), and post-discharge (73.0%). 10 Parents identified searching for information on prematurity, explanations of abbreviations, common medical problems, and available treatments, as well as information on infant care post-discharge. 6,10 While the Internet could be a beneficial resource for parents to access a breadth of information related to prematurity at their own pace, there are significant differences in health and care needs found within this highly sensitive population characterized by gestational age, birth weight, diagnoses, feeding methods, and severity of illness.…”
mentioning
confidence: 99%
“…10 Parents identified searching for information on prematurity, explanations of abbreviations, common medical problems, and available treatments, as well as information on infant care post-discharge. 6,10 While the Internet could be a beneficial resource for parents to access a breadth of information related to prematurity at their own pace, there are significant differences in health and care needs found within this highly sensitive population characterized by gestational age, birth weight, diagnoses, feeding methods, and severity of illness. 11 The care required to support an infant born extremely preterm (i.e.…”
mentioning
confidence: 99%